Willingness of mothers to vaccinate female adolescent children against cervical cancer among female faculty members of a Nigerian university (2016)
Background: With low level of cervical cancer screening in the developing world, there is need for exploiting other angles that could be effective in stemming the tide of high mortality and morbidity rate due to cervical cancer. The availability of effective prophylactic HPV vaccines gives new promise for a primary prevention strategy for HPV infection and cervical cancer. Research effort on mothers’ awareness and willingness to allow adolescent girl children between 9-13 years to get vaccinated against HPV will boost local literature and current effort aimed at combating the incidence and prevalence of cervical cancer in Africa. It is against this background that this study was designed to investigate willingness of mothers to vaccinate their girl children against HPV among female faculty members of the University of Ibadan, Ibadan. Methods: The descriptive survey research design was employed in the study while the population comprised female faculty members across all the faculties in the University of Ibadan. A sample of 100 respondents was drawn across five faculties in the university using a two stage sampling technique. The inclusion criterion is having a female child that is between age 9-13. The instrument for data collection was a self-developed and validated questionnaire and the process of data collection involved face-to-face administration by the research assistants supervised by the principal investigator. Generated data were analysed using descriptive statistics of frequency count and percentages. Result: The result of the study showed that although there is a high level of awareness on cervical cancer, the level of awareness on HPV vaccine was considerably low. This will in no little way affect willingness of mothers to have their female children vaccinated against HPV. Utilization of the HPV service will largely depend on the knowledgeable of its existence and benefits. Findings also showed that respondents’ willingness to have their children vaccinated against HPV is largely dependent on cost, availability and accessibility of the vaccine.Conclusion: Based on the findings of the study, it is concluded that there is low level of awareness on the availability of HPV vaccines among the population. It is also concluded that willingness to get girl children vaccinated against cervical cancer is dependent on cost, availability and accessibility. If members of the academic staff who are presumed to be knowledgeable about advancements in all spheres of the society including medical sciences reported low level of awareness of HPV vaccine, one wonders the level that will be reported by non-academic staff and even uneducated members of the society. It is therefore important to address the issue of availability, access and affordability to enhance the utilization of HPV vaccines.